Results of sinus trabeculectomy in treatment of patients with combination of glaucoma and cataract - N. G. Zavgorodnjaja; A. S. Sarzhevsky (Zaporožskij Medicinskij Žurnal)
Glaucoma is one of the most frequent reasons of vision decline and disability. One of methods of surgical treatment of glaucoma is an operation of filter type – sinus trabeculectomy.